Strategic Alignment as a Mechanism for Mediating Between Organizational Resources and Performance - Ikawati, Benida; Rofiqoh, Ifah (Oikonomia : Journal of Management Economics and Accounting, 2026)
This study examines the role of strategic alignment as a mediating mechanism between organizational resources and organizational performance. Although organizations invest heavily in IT capability, Big Data Analytics, Human Resource Analytics, and strategic HR practices, prior research frequently reports inconsistent and weak direct effects of these resources on performance outcomes. This study argues that the value of organizational resources is realized only when they are aligned with organizational strategy, processes, roles, and performance metrics. Using an explanatory quantitative design, data were collected from managers working in technology-intensive and knowledge-based organizations through a structured questionnaire. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test the mediation model. The results indicate that organizational resources do not have a significant direct effect on performance. However, organizational resources significantly influence strategic alignment, and strategic alignment significantly improves organizational performance. The mediation analysis confirms that strategic alignment fully mediates the relationship between resources and performance. These findings contribute theoretically by integrating the Resource-Based View with Strategic Alignment theory and offer practical implications for managers to prioritize alignment practices rather than focusing solely on resource acquisition.